Cultural Coexistence in Islamic History (Journal of the College of Education for Women, 2019)
The difference and pluralism among members of the same society is a fact undeniable and ignored, passed by the Quran, and confirmed by the Sunnah of the Prophet Mohammed in more than one occasion, so that the Apostle r placed a document included in its terms an agreement with the Jews, and recognized the coexistence between Muslims and Jews, which stems from the great principle of a tolerance, which recognizes the rights of others and the freedom to believe what is believed to be right, so it was incumbent upon us, and we live in rivalry repulsion and jealousies to recognize the principle of coexistence with the other, and accept it in accordance with the legitimate controls with pride of belonging to the Islamic religion, in this sense I suggested writing in this topic, I live in a country bedeviled Discord and rivalry between his sons, and only because they missed the concept of coexistence and the teachings of their religion and forgot how to deal with each other. The study concluded a group of results and recommendations, the most important of which are: The historical relationships of civilizations are not characterized by exchanging.